Chronic liver injury drives non‐traditional intrahepatic fibrin(ogen) crosslinking via tissue transglutaminase. (10th December 2018) - Poole, L. G.; Pant, A.; Baker, K. S.; Kopec, A. K.; Cline‐Fedewa, H. M.; Iismaa, S. E.; Flick, M. J.; Luyendyk, J. P.
Abstract : Essentials Fibrin clots are often implicated in the progression of liver fibrosis. Liver fibrosis was induced in transgenic mice with defects in clot formation or stabilization. Liver fibrosis and fibrin(ogen) deposition do not require fibrin polymerization or factor XIIIa. Fibrin(ogen) is an in vivo substrate of tissue transglutaminase in experimental liver fibrosis. Summary: Background: Intravascular fibrin clots and extravascular fibrin deposits are often implicated in the progression of liver fibrosis. However, evidence supporting a pathological role of fibrin in hepatic fibrosis is indirect and based largely on studies using anticoagulant drugs that inhibit activation of the coagulation protease thrombin, which has other downstream targets that promote fibrosis. Therefore, the goal of this study was to determine the precise role of fibrin deposits in experimental hepatic fibrosis. Methods: Liver fibrosis was induced in mice expressing mutant fibrinogen insensitive to thrombin‐mediated proteolysis (i.e. locked in the monomeric form), termed Fib AEK mice, and factor XIII A2 subunit‐deficient (FXIII −/− ) mice. Female wild‐type mice, FXIII −/− mice and homozygous Fib AEK mice were challenged with carbon tetrachloride (CCl4 ) twice weekly for 4 weeks or 6 weeks (1 mL kg −1, intraperitoneal). Results: Hepatic injury and fibrosis induced by CCl4 challenge were unaffected by FXIII deficiency or inhibition of thrombin‐catalyzed fibrin polymer formation (in Fib AEK mice). Surprisingly, hepatic deposition of crosslinked fibrin(ogen) was not reduced in CCl4 ‐challenged FXIII −/− mice or Fib AEK mice as compared with wild‐type mice. Rather, deposition of crosslinked hepatic fibrin(ogen) following CCl4 challenge was dramatically reduced in tissue transglutaminase‐2 (TGM2)‐deficient (TGM2 −/− ) mice. However, the reduction in crosslinked fibrin(ogen) in TGM2 −/− mice did not affect CCl4 ‐induced liver fibrosis. Conclusions: These results indicate that neither traditional fibrin clots, formed by the thrombin–activated FXIII pathway nor atypical TGM2‐crosslinked fibrin(ogen) contribute to experimental CCl4 ‐induced liver fibrosis. Collectively, the results indicate that liver fibrosis occurs independently of intrahepatic fibrin(ogen) deposition.